Oral pyruvate prevents high-intensity interval exercise-induced metabolic acidosis in rats by promoting lactate dehydrogenase reaction - Che, Kaixuan; Yang, Yanping; Zhang, Jun; Feng, Lin; Xie, Yan; Li, Qinlong; Qiu, Junqiang (Frontiers in Nutrition, 2023)
There is no denying the clinical benefits of exogenous pyruvate in the treatment of pathological metabolic acidosis. However, whether it can prevent exercise physiological metabolic acidosis, delay the occurrence of exercise fatigue, and improve the beneficial effects of exercise and its internal mechanism remain unclear. To address this gap, we randomly divided 24 male SD rats into 3 groups: one group was a control without exercise (CC, n = 8), and the other two groups were supplemented with 616 mg/kg/day pyruvate (EP, n = 8) or distilled water of equal volume (EC, n = 8). These groups completed acute high-intensity interval exercise (HIIE) after 7 days of supplementation. The acid metabolism variables were measured immediately after exercise including blood pH (pHe), base excess (BE), HCO3−, blood lactic acid and skeletal muscle pH (pHi). The redox state was determined by measuring the oxidised coenzyme I/reduced coenzyme I (nicotinamide adenine dinucleotide [NAD+]/ reduced NAD+ [NADH]) ratio and lactate/pyruvate (L/P) ratio. In addition, the activities of lactate dehydrogenase A (LDHA), hexokinase (HK), phosphofructokinase (PFK) and pyruvate kinase (PK) were determined by ELISA. Pyruvate supplementation significantly reversed the decrease of pHe, BE, HCO3− and pHi values after HIIE (p < 0.001), while significantly increased the activities of LDHA (p = 0.048), HK (p = 0.006) and PFK (p = 0.047). Compared with the CC, the NAD+/NADH (p = 0.008) ratio and the activities of LDHA (p = 0.002), HK (p < 0.001), PFK (p < 0.001) and PK (p = 0.006) were significantly improved in EP group. This study provides compelling evidence that oral pyruvate attenuates HIIE-induced intracellular and extracellular acidification, possibly due to increased activity of LDHA, which promotes the absorption of H+ in the LDH reaction. The beneficial effects of improving the redox state and glycolysis rate were also shown. Our results suggest that pyruvate can be used as an oral nutritional supplement to buffer HIIE induced metabolic acidosis.